Environmental Impact and Mitigation Approaches in Livestock Production Systems: A Review - , Nawal Kishor Singh; , Prachi Chandrakar; , Mahanthesh M.T; , Thomas Taye; , Indra Pratap Singh; , Vivek Pratap Singh; , Swarnalata Bara; , Udharwar Sanjaykumar Vithalrao (Archives of Current Research International, 2025)
Livestock production systems are critical to global food security, economic development, and rural livelihoods, yet they impose considerable environmental burdens. The environmental impacts and mitigation strategies associated with livestock systems, focusing on greenhouse gas emissions, land degradation, water pollution, biodiversity loss, and antimicrobial resistance. Ruminants such as cattle and buffalo are major contributors to methane emissions through enteric fermentation, while pig and poultry operations generate significant amounts of ammonia and nutrient-rich effluents that contaminate water resources. Intensive systems accelerate land-use change for feed crop cultivation, leading to soil erosion and forest fragmentation, whereas extensive pastoral systems often result in overgrazing and desertification in fragile ecosystems. Technological interventions, including low-emission diets, precision feeding, anaerobic digestion, and biogas recovery, have demonstrated potential to mitigate environmental footprints. Genetic improvement programs targeting feed efficiency and methane-reducing traits, alongside indigenous breed conservation, offer complementary strategies. The integration of Internet of Things (IoT), artificial intelligence (AI), and microbiome engineering enables real-time monitoring and reduction of emissions at the farm level. Socio-economic factors such as livelihood dependency, gender dynamics, and market-driven sustainability influence the adoption of climate-smart livestock practices. Challenges include high technology costs, lack of emission data, institutional fragmentation, and behavioural resistance among smallholders. Climate-resilient infrastructure and silvopastoral systems provide adaptive solutions aligned with both productivity and ecological integrity. Coordinated policy frameworks, public awareness programs, and financial incentives are essential to support sustainable transitions. Livestock systems contribute significantly to environmental change. A science-based, multi-disciplinary approach integrating technological innovation, farmer empowerment, and systemic policy reform can enhance sustainability without compromising food and livelihood security. Bridging knowledge gaps and fostering inclusive, adaptive livestock development pathways remain key to achieving long-term resilience and low-carbon agricultural transformation. Advancing sustainable livestock calls for coordinated policy, transdisciplinary research, and farmer-centric innovation, ensuring ecological balance without compromising food and livelihood security.